A Human Embryonic Stem Cell Model of Aβ-Dependent Chronic Progressive Neurodegeneration - Ubina, Teresa; Magallanes, Martha; Srivastava, Saumya; Warden, Charles D.; Yee, Jiing-Kuan; Salvaterra, Paul M. (Frontiers in Neuroscience, 2019)
We describe construction and phenotypic analysis of a human embryonic stem cell model of progressive Abeta-dependent neurodegeneration (ND) with potential relevance to Alzheimer’s disease (AD). We modified one allele of the normal APP locus to directly express a secretory form of Abeta40 or Abeta42, eliminating the need for amyloidogenic APP proteolysis. Following neuronal differentiation edited cell lines specifically accumulate aggregated/oligomeric Abeta, exhibit a synaptic deficit and have an abnormal accumulation of endolysosomal vesicles. Edited cultures progress to a stage of overt ND. All phenotypes appear at earlier culture times for Abeta42 relative to Abeta40. Whole transcriptome RNA-Seq analysis identified 23 up and 70 down regulated genes (DEGs) with similar directional fold change but larger absolute values in the Abeta42 samples suggesting common underlying pathogenic mechanisms. Pathway/annotation analysis suggested that down regulation of extracellular matrix and cilia functions are significantly overrepresented. This cellular model could be useful for uncovering mechanisms directly linking Abeta to neuronal death and as a tool to screen for new therapeutic agents that slow or prevent human ND.